The voices of me in the Las voces bajas by Manuel Rivas (XXI Century. Spanish Literature and Culture, 2013)
An autobiographical work of Manuel Rivas is studied through the three stages that writing crosses: Storyboard (2010), a collection of articles, As voces baixas (2012), the first novel transposition in Galician and Las voces bajas (2012), author's self-translation in Castilian. Throughout the writing process and in the course of genres and languages, self-referential narrative reveals proficuos elements for reflection on the determination, perspective and vision of the “I” in the present Narrative.
Keywords: Manuel Rivas; Las voces bajas; reference